Accurate determination of damaged subsurface layers in machined Inconel 718. Issue 9 (February 2017) - Touazine, Heithem; Jahazi, Mohammad; Bocher, Philippe
Abstract The machining of high strength materials used in aeronautical applications generates damage on the subsurface layer, which can significantly affect the fatigue life of the machined components. It is then important to distinguish between the damages due to machining from those caused by mechanical polishing operations used for sample observation. In this study, a new method is proposed to characterize and quantify properly the affected layer by machining and eliminating the impact from the defects originated during mechanical polishing. A protective layer of nickel coating was deposited on the machined surface. An optimum thickness of 100 μm was determined for the nickel layer to avoid any damage to the subsurface layer during sample preparation. The subsurface layer was analyzed using an automatic Knoop microhardness machine, laser-digital microscope, and electron backscatter diffraction (EBSD) microscopy.